DEVELOPMENT OF DIGITAL COMICS MEDIA BASED ON I-SPRING ON PANCASILA VALUES MATERIAL FOR GRADE IV SDN 2 KUTOANYAR, TULUNGAGUNG REGENCY - Ratna Ayu Ambarwati; Wahyudi Wahyudi; Bagus Amirul Mukmin (PIONIR: JURNAL PENDIDIKAN, 2024)
This study aims to develop and test the validity, practicality, and effectiveness of I-Spring-based Digital Comic Media on Pancasila Education subjects in class IV SDN 2 Kutoanyar. By using the ADDIE development model which consists of five main stages: Analysis, Design, Development, Implementation, and Evaluation, this research begins with problem identification through observations and interviews at the school. The material was developed using Microsoft PowerPoint application and converted into an interactive multimedia format with i-Spring. Media validation was carried out by material experts and media experts, giving 88% and 92% marks respectively, which accumulated to 90%, indicating that the media was very valid. Implementation involved limited trials and extensive trials involving students and teachers, showing excellent practicality with an accumulative score of 93.5% from student and teacher responses, indicating the media was very practical and did not require revision. The effectiveness test through evaluation questions (Post Test) showed positive results, with the average score of students reaching 90.4%, exceeding the Minimum Completeness Criteria (KKM) of ≥75, which means that this media is very effective in increasing students' understanding and enthusiasm for Pancasila values material. Thus, I-Spring-based Digital Comic Media can be recommended as a valid, practical, and effective learning media to be applied in Civics education in elementary schools.Keywords: Digital Comic Media for PPKn Learning Development Model ADDIE.